2022
DOI: 10.1038/s41598-022-21060-3
|View full text |Cite
|
Sign up to set email alerts
|

Polar amplification comparison among Earth’s three poles under different socioeconomic scenarios from CMIP6 surface air temperature

Abstract: The polar amplification (PA) has become the focus of climate change. However, there are seldom comparisons of amplification among Earth’s three poles of Arctic (latitude higher than 60 °N), Antarctica (Antarctic Ice Sheet) and the Third Pole (the High Mountain Asia with the elevation higher than 4000 m) under different socioeconomic scenarios. Based on CMIP6 multi-model ensemble, two types of PA index (PAI) have been defined to quantify the PA intensity and variations, and PAI1/PAI2 is defined as the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…S1). In line with former studies 12,14 , a higher degree of amplification over the Arctic ocean is found in the mid-21st century (Fig. S2) or in a weaker emission scenario (Fig.…”
Section: Quantifying Uncertainties In Cmip6 Projections Of the Arctic...supporting
confidence: 91%
See 3 more Smart Citations
“…S1). In line with former studies 12,14 , a higher degree of amplification over the Arctic ocean is found in the mid-21st century (Fig. S2) or in a weaker emission scenario (Fig.…”
Section: Quantifying Uncertainties In Cmip6 Projections Of the Arctic...supporting
confidence: 91%
“…This value is much higher than the 2.6 ratio found at the end of the 21 st century (Fig. S9a), which is fully consistent with the fact that the regional Arctic feedbacks are time-evolving and forcingdependent 12,14 . This finding suggests that some Arctic feedbacks may be also sensitive to the base state and thus to biases in climate models.…”
Section: Constraining and Attributing Recent Changes In Arctic Climatesupporting
confidence: 86%
See 2 more Smart Citations
“…Climate change is a serious and escalating problem globally. 1,2 It is primarily attributed to the greenhouse effect of atmospheric CO2. 3 The concentration of atmospheric CO2 has reached over 400 ppm by 2013 and has been predicted to further increase in the near future.…”
Section: Introductionmentioning
confidence: 99%